Low temperature neutron diffraction studies on Co(Cr1−xFex)2O4 (x = 0.05 and 0.075). Issue 96 (29th September 2016) - Kumar, Ram; Padam, R.; Das, Debashish; Rayaprol, S.; Siruguri, V.; Pal, D.
Abstract : We report the magnetic structures of an Fe substituted cobalt chromite system, Co(Cr1− x Fe x )2 O4 ( x = 0.05 and 0.075), determined from the analysis of temperature dependent neutron diffraction measurements. Abstract : We report the magnetic structures of an Fe substituted cobalt chromite system, Co(Cr1− x Fe x )2 O4 ( x = 0.05 and 0.075), determined from the analysis of temperature dependent neutron diffraction measurements. The ferrimagnetic transition temperature ( T c ) was found to increase from ∼110 K to ∼118 K with the increase of Fe substitution. Neutron diffraction studies reveal magnetic peaks below the transition temperature, T c . In addition, we observed a broad hump below the Bragg reflection (111), indicative of diffuse scattering from short-range magnetic interactions coexisting with long range magnetic order below T c . The length scale of this short range magnetic order shows unusual non-monotonic temperature dependence. The bulk magnetization data reveals that the magneto-structural transition ( T s ) remains unaffected with temperature in both the compounds. This magneto-structural transition at T s gives rise to the magnetic satellite peaks of the conical spin-spiral structure which can be indexed as (220)* and (002)* with a magnetic structure using an incommensurate propagation vector. With a further lowering of the temperature around the lock-in transition, T L (∼10 K), the incommensurate peak of the propagation vector (0.62, 0.62, 0) splits into two peaks with a deviation of 0.02 in Q -value from the centre.